Degenerative Spine surgery: Our perspective - Acharya, Samir (Nepal Journal of Neuroscience, 2025)
Degenerative spinal diseases of the lumbar region remain one of the leading causes of disability across various age groups, significantly affecting patients’ quality of life. When conservative management fails or when neurological deficits are evident, surgical intervention becomes the mainstay of treatment in such cases.